«Two "fellow-pragmatists"»: Giovanni Papini and William James (Nóema, 2015)
This article aims to examine Giovanni Papini’s Pragmatism (undoubtedly the most noticeable and  unusual  within  Italian  pragmatists), by  referring it particularly to  William James’ thought;  more  specifically,  it  aims  to  enlighten  both  the  agreeable cooperation  and  the  mutual influence and admiration between Papini and James. In order to do this, in this paper the steps of the development  of  Papini’s  Pragmatist  theory  will be  retraced,  by  pointing  out  both  its  bond  with Jamesian speculation (without forgetting its Bergsonian feature) and its originality and theoretical relevance, able to assert itself also beyond the Italian borders.
Keywords: Pragmatism; Papini; James; Bergson; Metatheory of Action